Analisis Tingkat Profitabilitas Perbankan Syariah di Indonesia - Fatmawati1, Nur Lailatul; Hakim, Abdul (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2020)
The ability of banks to generate profitability greatly impacts the growth and development of sharia banking. In maintaining and enhancing the growth of sharia banking, several components, both internal and external, are needed. The low profitability of banks indicates that banks are not good in their performance. Profitability is still something that is always wanted to be improved by Islamic banking because it sees the movement of Islamic banking growth that is still lagging far behind that of conventional banking. will be able to increase profitability. The purpose of this study is to determine the effect of FDR, BOPO, and exchange rates on the level of profitability (ROA). To determine the effect of NPF and interest rates on the level of profitability (ROA). To find out the influence of Mudharabah Financing, musyarakah financing and murabahah financing on profitability (ROA). This research uses a quantitative approach. The type of data used in this study is secondary data in the form of time series data. This study shows that FDR, BOPO, and exchange rates have a negative and significant effect on the level of profitability (ROA). NPF and interest rates have a negative and not significant effect on the level of profitability (ROA). Mudharabah financing, musyarakah financing and murabahah financing have a positive and not significant effect on profitability (ROA).